2020
DOI: 10.1177/0706743720905201
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of the Clinical Characteristics Associated with Alcohol and Cannabis use in Early Phase Psychosis

Abstract: Objective: Alcohol and cannabis misuse are common in patients with early phase psychosis (EPP); however, research has tended to focus primarily on cannabis misuse and EPP outcomes, with a relative lack of data on alcohol misuse. This retrospective cross-sectional EPP study investigated the relationship between cannabis, alcohol, and cannabis combined with alcohol misuse, on age, gender, psychotic, depressive and anxiety symptom severity, and social/occupational functioning, at entry to service. Methods: Two-hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…The eligibility criteria are as follows: (1) meet the criteria for a first episode of psychosis defined as the first illness episode involving psychosis symptoms; (2) meet DSM-5 (Diagnostic and Statistical Manual of Mental Disorders, 5th Edition) criteria for a psychotic disorder and a lifetime or current cannabis use disorder (up to 45% of people with a first episode of psychosis will meet the criteria for cannabis use disorder [ 16 , 47 , 48 ]; patients diagnosed with cannabis-induced psychosis by definition meet the criteria for both conditions [ 49 ] and will be eligible); (3) be between the ages of 16 and 30 years; (4) self-identify as a Black African or Black Caribbean first- or second-generation immigrant (English speaking), or belong to any ethnic group; (5) be a client of an early psychosis intervention with up to 12 months of service; and (6) be fluent in English.…”
Section: Methodsmentioning
confidence: 99%
“…The eligibility criteria are as follows: (1) meet the criteria for a first episode of psychosis defined as the first illness episode involving psychosis symptoms; (2) meet DSM-5 (Diagnostic and Statistical Manual of Mental Disorders, 5th Edition) criteria for a psychotic disorder and a lifetime or current cannabis use disorder (up to 45% of people with a first episode of psychosis will meet the criteria for cannabis use disorder [ 16 , 47 , 48 ]; patients diagnosed with cannabis-induced psychosis by definition meet the criteria for both conditions [ 49 ] and will be eligible); (3) be between the ages of 16 and 30 years; (4) self-identify as a Black African or Black Caribbean first- or second-generation immigrant (English speaking), or belong to any ethnic group; (5) be a client of an early psychosis intervention with up to 12 months of service; and (6) be fluent in English.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis showed that in samples of patients treated in FEP clinics, between 29 and 38% used cannabis ( 40 ). Prior to legalization of cannabis in Canada, a study of a sample of patients with recent diagnoses of psychosis reported that 13% were misusing alcohol-only, 21% cannabis-only, and 50% both alcohol and cannabis ( 41 ). Cannabis may be specifically linked to AB among persons with severe mental illness.…”
Section: Additional Factors Promoting Abmentioning
confidence: 99%
“…Cannabis users with psychosis have an earlier onset of illness, increased symptom severity, poorer adherence to psychiatric medication, poorer functional outcomes, higher relapse rates and longer hospital stays compared with non-users. 5,6,7,8,9,10,11 In addition, people with schizophrenia spectrum and other psychotic disorders and comorbid cannabis use tend to have poorer psychosocial functioning, homelessness, violence, incarceration and increased burden of care for families. 4,12,13,14 having been reported.…”
Section: Introductionmentioning
confidence: 99%